About-face: the United States and Portuguese colonialism in 1961 - Rodrigues, L. N. (e-Journal of Portuguese History, 2004)
In 1961, the Kennedy Administration decided to adopt a new African policy, supporting self- determination and independence. This change occurred while the war against Portuguese colonial rule erupted in Angola. Acting in accordance with the principles adopted by the administration, the American Ambassador in Lisbon informed the Portuguese government of this new policy and recommended the urgent adoption of reforms in the Portuguese territories in Africa. When, in March, the situation in Angola was brought to debate in the United Nations, the United States voted in favor of a defeated resolution condemning Portuguese colonialism. Needless to say, this action provoked a serious crisis in Portuguese-American relations.